Bibliometric Analysis: Trend of ICT and RME Researches - Edi Supriyadi; Jarnawi Afgani Dahlan; Darhim Darhim; Joseph Taban (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
Research in both ICT and RME is expanding at a breakneck pace. The growth of research in engineering can be tracked by one type of analysis known as bibliometric analysis. This analysis can be used to identify the number of scholarly publications on ICT and RME. This study is of a quantitative and descriptive nature. Researchers are interested in examining the development of ICT and RME, as well as the distribution pattern of publications in Scopus, which is based on research affiliations, research themes, and scientific journals. For the goals of data analysis, reduction, visualization, and mapping, respectively, Bibliometrix R-tool and BiblioShiny were utilized throughout the course of this research. Scopus bibliometric study finds that between the years 1999 and 2022, there was a shift in the number of research articles that could be located in the Scopus online database that were associated with ICT and RME. The year 2020 was the year that this publication - Journal on Education and Information Technologies - reached its zenith. In terms of the quantity of documents generated, research in the fields of ICTÂ is dominated by writers from the Czech Republic and the Netherlands.